PENERAPAN ALGORITMA KLASIFIKASI C4.5 REVIEW PELANGGAN DALAM BERTRANSAKSI PADA PT. DAPOER MAMIH - Wahana Indra Komala; Andri Yansah; Resti Pebrina; Suhardjono Suhardjono (Jurnal Riset Sistem Informasi, 2026)
Wahana Indra Komala (19242542), Andri Yansah (19242561), Resti Pebrina (19242563), Implementation of C4.5 Classification Algorithm Customer Review in Transactions at PT. Dapoer Mamih Dapoer Mamih is a company engaged in the culinary field and is committed to providing the best service to its customers. One way to radiate service quality and customer satisfaction is by analyzing customer Reviews. This study aims to classify customer Reviews in transactions using the C4.5 classification algorithm. The C4.5 algorithm was chosen because of its ability to form an effective Decision Tree in handling categorical and numeric data and handling missing data values. The data used in this study came from customer Reviews collected by the company. The analysis process begins with the data preprocessing stage, attribute selection, model training, and evaluation of model classification performance. The results of the study show that the C4.5 algorithm is able to group customer Reviews into certain categories such as positive, neutral, and negative with an adequate level of accuracy. These findings can be the basis for companies to make strategic decisions in improving service quality and customer experience. Keywords: Classification; C4.5; Customer Reviews; Decision Trees; Data Mining.